ANALYSIS OF FACTORS AFFECTING THE LEVEL OF CONSUMPTIVE BEHAVIOR AMONG STIEPARI SEMARANG STUDENTS LIVING IN BAWEN BOARDING HOUSES - Ziliwu, Ester; Satato, Yuniarto R (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study examined factors influencing consumptive behavior among STIEPARI Semarang students in Bawen boarding houses. Using quantitative analysis with 150 respondents, the research identified four significant predictors: peer influence, social media exposure, financial literacy, and family income background, collectively explaining 54.7% of variance. The boarding environment intensified peer influence while reducing parental oversight, with 81.3% of students exhibiting moderate to high consumptive tendencies. Status consumption, convenience-based spending, and impulsive purchasing were predominant behaviors, while longer boarding residence correlated with higher consumptive tendencies. Findings suggest a need for targeted financial literacy programs, media awareness initiatives, and improved parental financial socialization before students transition to independent living. This research helps explain how residential context mediates consumption patterns and offers practical conclusions for educational institutions promoting responsible consumption. Keywords: Consumptive Behaviour; Boarding House Students; Peer Influence; Financial Literacy; Social Media Exposure